Technology Transformation in Islamic Religious Education Student Learning in Facing 2025 Trends Using SAMR and TPACK Models - Wiene Surya Putra; Agus Salim; Sri Adhi (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study examines how 2025 educational technology trends are transforming Islamic Religious Education (IRE) student learning and how the SAMR and TPACK frameworks guide that integration. A convergent-parallel mixed-methods design was used in Indonesian IRE institutions: surveys of students and educators quantified perceived impacts and levels of integration, while interviews and focus group discussions explored experiences and challenges; quantitative data were analyzed with descriptive/inferential statistics and qualitative data with thematic analysis. Results indicate strong perceived benefits of AI-driven personalization, VR/AR, and gamification for engagement and accessibility, with hybrid models supporting flexibility. However, classroom practice is concentrated at lower SAMR levels (Substitution, Augmentation), with limited movement to Modification/Redefinition. Educators report high content and pedagogical knowledge, moderate technological knowledge, and the lowest confidence in integrated TPACK; barriers include workload, training gaps, infrastructure, and preserving Islamic ethical values. We conclude that IRE can leverage emerging technologies to enrich learning, but true transformation requires targeted, context-specific TPACK professional development, curriculum redesign toward higher-order SAMR tasks, robust ethical/digital-literacy safeguards, and equitable infrastructure investment